Antisuicidal Effects in Mood Disorders: Are They Unique to Lithium? - Tondo, Leonardo; Baldessarini, Ross J. (Pharmacopsychiatry, 2018)
Introduction Suicidal behavior is strongly associated with depression in major depressive (MDD) and bipolar (BD) disorders, especially with associated behavioral activation, dysphoria, or agitation. A rare intervention with evidence of suicide risk-reducing as well as mood-stabilizing effects in mood disorder patients is lithium.Methods We reviewed available research evidence on associations of long-term treatment with lithium with risk of suicidal behavior. We meta-analyzed 12 randomized trials in 10 reports (with at least 1 suicide in either treatment arm) including both BD and MDD subjects, with particular attention to comparisons of lithium with placebo or other pharmacological treatments. We also summarized ecological studies on lithium concentration in local drinking water and reported suicide rates.Results We found substantial reduction of risks of suicide and attempts with long-term lithium treatment, particularly in depressive phases of BD and in MDD. Risk of suicidal behavior was higher in mixed (agitated-dysphoric) states than in manic or hypomanic periods. Risk of suicide fatality, specifically, was lower with lithium than with placebo and probably with mood-altering anticonvulsants or antidepressants.Discussion Long-term treatment with lithium has growing evidence of suicide- and attempt-sparing effects, probably greater than with anticonvulsants or antidepressants; antipsychotics remain to be tested adequately. However, the ethical and scientifically adequate design and conduct of trials of treatments aimed at suicide prevention remain challenging and underdeveloped.
Keywords: anticonvulsants; antidepressants; antipsychotics; bipolar I and II disorders; lithium; major depressive disorder; suicide